Middle class urbanism is a policy issue. - Mazzolini, Anna (My University, 2020)
Many different voices have arisen over the last years regarding the further evidence on urbanization directions in the Global South. New, diverse and multi-agency urbanization patterns and their transformative impacts on countries ́ policies, planning apparatus and land management have been at the core of the recent debate on southern urbanism. Among factors such as the role of foreign investments on urban planning, the increasing contribution of the “informal” economies in the city development and economies, and the threat of new “unsustainable” urban trends such as sprawl, congestion and collapse of conventional planning systems, the urban middle class appears to be an intersecting and recurrent actor silently penetrating and influencing all the factors mentioned above. Current rising investments in Africa’s cities which are often described as entirely new cities or planned, self-contained enclaves, are related to this new urban actor. On the other hand, paradoxically it is the urban middle class that is seen as the sole actor able to create a more equitable urban environment. Beyond pure spatial and policy analysis, what is at stake is to capture more conceptual clarity on these issues, and this is a complex and long-lasting issue. After almost two years of Intense research, the Middle Class Urban- ism Project is pleased to share the first brief on this topic and to introduce its interdisciplinary and positively deconstructive research approach.
Keywords: Urbanisierung; Stadtwachstum; Wohnungsneubau; Mittelschicht; Entwicklungsland; Sozioökonomischer Wandel; Fallbeispiel